Epistemology of Basic Concepts of Spiritual and Physical Thaharah: Analysis of The Benefits of Ablution Spiritually and Physically - Meirison , Meirison; Insani , Fadhilah; Andini , Zahara (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
This article aims to explain the purpose of purification in various forms. Purification outwardly and inwardly will be obtained when following the rules given by the Qur'an and Hadith. Purification (thaharah) is one of the legal conditions in performing Salat. When we start performing an act of worship such as Salat, many of us are not right or wrong when taking ablution or sometimes after removing many unclean impurities. I did a literature study with a descriptive analysis approach and found that three ways can be pure: bathing, ablution, and tayammum. The tools used for bathing and ablution are water and for tayammum using soil (dust). As we know, Tayammum can only be done when there is no water and in a state of pain. Purification also removes not only the contaminated feces but also the inner. In purifying, using absolute water or using soil (dust) must meet certain conditions. By doing purification according to the provisions of Rasulullah, then we will get external and internal purity. Keywords: Epidemiology, Concept, Spiritual, Physical, Thaharah